Real time forecasting in the coastal zone: Stream power in the lower Mississippi River - Laura Manuel; Ehab Meselhe; Kelin Hu; Arnejan van Loenen; Thies Blokhuijsen; Md Nazmul Azim Beg (Journal of Hydrology: Regional Studies)
Study region: This study details the development of a real time forecasting system for the coastal zone of the Northern Gulf of Mexico providing a twice daily, ten-day forecast of two-dimensional hydrodynamics. The Mississippi River Delta is the primary entrance to over 2300 miles of commercial waterway and faces year-round dredging and evolving unregulated natural outlets. The provision of real time forecast data is becoming increasingly important for navigation and various ecosystem services in the Gulf region. Study focus: Advances in hydrologic forecasting are swiftly progressing due to advances in computing technology, modeling techniques, and data availability. However, coastal zones remain challenging for forecasting due to the complexity of coastal processes governing the dynamics in these regions. A promising solution to predicting coastal conditions is the development of process-based modeling approaches that represent the transition zone, operating in a forecasting mode. New hydrological insights for the region: Primary outputs of the forecasting system, which are not produced by public agencies at the time of this study, include the provision of reach scale stream power forecasts for the Lower Mississippi River profile from Baton Rouge, LA to the Gulf of Mexico and detailed forecasts of flow partitioning among the natural outlets near the Mississippi River Delta. This study demonstrates a forecasting system using a high-resolution model with functionalities that open services to groups besides traditional early warning users.